Manajemen Pendidikan Entrepreneur di Pondok Pesantren: Model, Strategi, dan Tantangan - Widodo, Wahyudi (TAUJIH: Jurnal Pendidikan Islam, 2025)
This study aims to describe the models, management strategies, and challenges in implementing entrepreneurship education in Islamic boarding schools. Using a qualitative case study approach. The findings reveal that there reveal four main models in entrepreneurship education in Islamic boarding schools, namely an integrated model between the diniyah curriculum and entrepreneurship, an extracurricular model based on business units, an internship or business incubation model, and an independent economic model based on the Islamic boarding school community. The applied management strategies include the stages of vision and curriculum planning, organizing entrepreneurial structures, implementation based on direct practice (learning by doing), and thematic and continuous evaluation. The main obstacles in its implementation include limited professional human resources, minimal facilities and access to technology, weak partnership networks, and the absence of national regulations that support entrepreneurship education in Islamic boarding schools. The study recommends strengthening human resource capacity, designing a hybrid curriculum based on Islamic values ​​and modern entrepreneurial principles, policy support from the government, and expanding partnership networks as strategic steps towards independence and sustainability of entrepreneurship education in Islamic boarding schools.